Ileocolic resection is associated with increased susceptibility to injury in a murine model of colitis - Perry, Troy (PLoS One, 2017)
Ileocolic resection (ICR) is the most common intestinal resection performed for Crohn's disease, with recurrences commonly occurring at the site of the anastomosis. This study used an animal model of ICR in wild-type mice to examine immunologic changes that developed around the surgical anastomosis and how these changes impacted gut responses to minor acute injury. ICR was performed in adult 129S1/SvlmJ mice and results compared with mice receiving sham or no surgery. Dextran sodium sulfate was given either on post-operative day 9 or day 24 to evaluate immune responses in the intestine both immediately following surgery and after a period of healing. Fecal occult blood measurements and animal weights were taken daily. Cytokine levels were measured in ileal and colonic tissue. Bacterial load in the neo-terminal ileum was measured using qPCR. Immune cell populations in the intestinal tissue, mesenteric lymph nodes, and spleen were assessed using flow cytometry. Cytokine secretion in response to microbial products was measured in isolated mesenteric lymph nodes and spleen cells. ICR resulted in an initial elevation of inflammatory markers in the terminal ileum and colon followed by enhanced levels of bacterial growth in the neo-terminal ileum. Intestinal surgical resection resulted in the recruitment of innate immune cells into the colon that exhibited a non-responsiveness to microbial stimuli. DSS colitis phenotype was more severe in the ileocolic resection groups and this was associated with local and systemic immunosuppression as evidenced by a reduced cytokine responses to microbial stimuli. This study reveals the development of an immune non-responsiveness to microbial products following ileocolic resection that is associated with enhanced levels of bacterial growth in the neo-terminal ileum. These surgical-induced altered immune-microbial interactions in the intestine may contribute to disease recurrence at the surgical anastomosis site following ileocolic resections in patients with Crohn’s disease.